2014
DOI: 10.14233/ajchem.2014.16082
|View full text |Cite
|
Sign up to set email alerts
|

A New Cytotoxic Stilbenoid from Arundina graminifo

Abstract: A new stilbenoid, gramniphenol K (1) was isolated from Arundina graminifolia. Its structure was elucidated by spectroscopic methods including extensive 1D-and 2D-NMR techniques. The cytotoxicity of gramniphenol K was evaluated against five human tumor cell lines, and it showed cytotoxicity against A549, SHSY5Y and MCF7 cells with IC50 values of 6.2, 7.5 and 4.7 µM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Arundina graminifolia (D. Don) Hochr., a species widely distributed in subtropical Asia and known as bai-yang-jie in Chinese, has a long history of use as one of the major drugs in a formula “BaoGan Capusle” with the efficacy of heat clearing and detoxifying, dispersing blood and relieving pain, reducing inflammation and promoting urination and so on [1]. Previous phytochemical investigation focusing on the chloroform and ethyl acetate exacts of A. graminifolia had resulted in the separation of stilbenoids [2,3,4], phenols [5,6,7], flavonoids [8,9] and other ketones [3,10,11]. However, the works on the polar parts of the plant are few.…”
Section: Introductionmentioning
confidence: 99%
“…Arundina graminifolia (D. Don) Hochr., a species widely distributed in subtropical Asia and known as bai-yang-jie in Chinese, has a long history of use as one of the major drugs in a formula “BaoGan Capusle” with the efficacy of heat clearing and detoxifying, dispersing blood and relieving pain, reducing inflammation and promoting urination and so on [1]. Previous phytochemical investigation focusing on the chloroform and ethyl acetate exacts of A. graminifolia had resulted in the separation of stilbenoids [2,3,4], phenols [5,6,7], flavonoids [8,9] and other ketones [3,10,11]. However, the works on the polar parts of the plant are few.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, it used to cure rheumatism (Hossain, 2009 ). Previous studies have reported stilbenoids as the major secondary metabolites in bamboo orchid, revealing the structural diversity of phenanthrenes (Liu et al, 2005 ), diphenylethylenes (Hu et al, 2013b ; Li et al, 2013a ; Gao et al, 2014 ; Meng et al, 2014 ; Yang et al, 2014 ), bibenzyls (Majumder and Ghosal, 1993 ; Du et al, 2014 ), and other phenolic compounds (Gao et al, 2012 ; Hu et al, 2013a ; Lidan et al, 2013 ; Li et al, 2013b ; Niu et al, 2013 ). Bibenzyls are effective antitumor agents due to their antioxidant and cell-protective properties (Gong, 2003 ; Zhang et al, 2007 ; Barbosa et al, 2009 ; Li et al, 2010 ; Su, 2011 ; Cai et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%